Popova and Smirnov’s Sudden Change of Hearts as Seen in Anton Chekov’s The Bear - Fetri Reni; Irwan Sumardi (Fakultas Sastra Universitas Ekasakti, 2018)
The study in this the drama of The Bear by Anton Chekov. This drama depicts a widow and debt collector. The problem in the drama of The Bear is on personality and character changes. This research uses observation method with note-taking technique and uses interpretation in analyzing data. For this reason, the theory of Sigmund Freud's (Id, Ego, Super-ego) is used. From the results of this study the authors found the characters of Popova and Smirrnov, in which Smirnov was actually a kind, young, beautiful, and Popova who was kind, romantic but rude. The cause of the change in Popov's character is based on his loneliness and Smirnov is based on economic needs. In Psychology Smirnov's personality who wants money (Id) and Popov want to force himself to duel with Smirnov (Ego) regardless of people in the surrounding environment, especially Luka as a helper of Popov (Super-Ego) in their quarrels and unwittingly emerge a feeling of love between Popova and Smirnov and finally they fall in love.